2001
DOI: 10.1104/pp.127.1.108
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Two P450 Enzymes, CYP83B1 and CYP83A1, in Auxin Homeostasis and Glucosinolate Biosynthesis

Abstract: The first committed step in the biosynthesis of indole glucosinolates is the conversion of indole-3-acetaldoxime into an indole-3-S-alkyl-thiohydroximate. The initial step in this conversion is catalyzed by CYP83B1 in Arabidopsis (S. Bak, F.E. Tax, K.A. Feldmann, D.A. Galbraith, R. Feyereisen [2001] Plant Cell 13: 101-111). The knockout mutant of the CYP83B1 gene (rnt1-1) shows a strong auxin excess phenotype and are allelic to sur-2. CYP83A1 is the closest relative to CYP83B1 and shares 63% amino acid sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(156 citation statements)
references
References 52 publications
5
145
0
2
Order By: Relevance
“…The ref2 mutant has decreased lignin content and Ϸ3-fold-reduced sinapate ester levels (29). The ref2 mutant is defective in CYP83A1, one of the two oxime-metabolizing cytochrome P450s in glucosinolate biosynthesis (30,31). It has been suggested that accumulation of oximes or their degradation products perturbs the biosynthesis of phenylpropanoids (29).…”
Section: Discussionmentioning
confidence: 99%
“…The ref2 mutant has decreased lignin content and Ϸ3-fold-reduced sinapate ester levels (29). The ref2 mutant is defective in CYP83A1, one of the two oxime-metabolizing cytochrome P450s in glucosinolate biosynthesis (30,31). It has been suggested that accumulation of oximes or their degradation products perturbs the biosynthesis of phenylpropanoids (29).…”
Section: Discussionmentioning
confidence: 99%
“…MYB28 (At5g61420, also called PRODUCTION OF METHIONINE-DERIVED GLUCOSINOLATE1), which is a positive regulator for the production of aliphatic GSLs at basal levels in Arabidopsis (Hirai et al, 2007), was down-regulated by both JA and RGA (Supplemental Table S8). In addition, two cytochrome P450 family genes encoding CYP79B2 and CYP83A1, which are involved in the production of indole and aliphatic GSLs (Hull et al, 2000;Bak and Feyereisen, 2001), were also down-regulated by RGA. Identification of these genes involved in GSL production suggests that the interaction between the JA pathway and DELLA proteins may control amino acid metabolism during stamen development.…”
Section: Expression Of Rga-regulated Genes In Different Floral Organsmentioning
confidence: 99%
“…AJ270. The deduced amino acid sequences of orf3, 4,5,6,7, and 8 displayed 82.8, 85.9, 96.4, 98.6, 98.6, and 73.2% identity to those of NHase regulator 2, NHase regulator 1, amidase, NHase R-subunit, NHase -subunit, and NHase activator of Rhodococcus sp. N-771, respectively.…”
Section: Effects Of Various Compounds On the Enzyme Activitymentioning
confidence: 99%
“…N-771, respectively. The deduced amino acid sequences of orf4, 5,6,7, and 8 displayed 98.0, 96.4, 98.6, 98.6, and 98.0% identity with those of Rhodococcus sp. AJ270, respectively.…”
Section: Effects Of Various Compounds On the Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation